Widespread occurrence of an emerging fungal pathogen in heavily traded Chinese urodelan species. Issue 4 (1st February 2018) - Yuan, Zhiyong; Martel, An; Wu, Jun; Van Praet, Sarah; Canessa, Stefano; Pasmans, Frank
Abstract: Understanding introduction routes for wildlife pathogens is vital for the development of threat abatement plans. The chytrid fungus Batrachochytrium salamandrivorans (Bsal) has recently emerged in Europe, where it is considered to be a serious threat for urodelan conservation. If the highly diverse Chinese urodelans were to constitute a Bsal reservoir, then the significant international trade in these species may vector Bsal into naïve urodelan communities. Here, we analyzed a total of 1, 143 samples, representing 36 Chinese salamander species from 51 localities across southern China for the presence of Bsal. We found Bsal was present across a wide taxonomic, geographical, and environmental range. In particular, Bsal DNA was detected in 33 samples from the genera Cynops, Pachytriton, Paramesotriton, Tylototriton, and Andrias, including the heavily traded species Paramesotriton hongkongensis and Cynops orientalis . The true Bsal prevalence across our data set was estimated between 2% and 4%, with a maximum of 50% in a population of P. hongkongensis . Even at this overall relatively low Bsal prevalence, the exportation of millions of animals renders Bsal introduction in naïve, importing countries a near certainty, which calls for the urgent implementation of proper biosecurity in the international wildlife trade.